Potentiometric Titration of Acid Soils From Peninsular Malaysia - Jusop, Shamsuddin; Tessens, Eddy (1983)

(untitled)
The study indicates the dominance of Al in controlling the acidity of acid Peninsular Malaysian soils. The buffering action of the soils is dominated by Al below pH 5.5 and by the clay minerals, mainly kaolinite, at pH above pH 5.5. The rate of extraction of Al from the soils depends on the concentration of the extracting solution. Lime requirement of the soils can be obtained by multiplying the base needed to raise the pH of the soil to 5.5 by a factor 1.3.